Perbanyakan In Vitro Dendrobium Indonesia Raya ‘Ina’ melalui Embriogenesis Somatik Berbasis Sistem Bioreaktor - Rachmawati, Fitri; Wiendi, Ni Made Armini; Mattjik, Nurhajati Ansori; Purwito, Agus; Winarto, dan Budi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTAn effective and efficient in vitro propagation system has important roles in preparing and producing high quality-seedlings of Dendrobium for commercial scale. The objective of this research was to establish an effective and efficient embryogenic callus (EC) proliferation method using bioreactor system and regeneration EC into plantlet for producing high quality seedlings of Dendrobium Indonesia Raya ‘Ina’. Differences in callus densities (5, 10, 15, and 20 g callus in 250 mL medium), aeration levels (2.5, 5.0, and 10.0 O2 volume  per  medium volume per minute; vvm), and regeneration media half-strength MS and 2 g L-1 NPK (32:10:10) combinated by 0.00, 0.05 mg L-1 BA, 150  mL L-1 coconut water and their combinations were tested in this experiment. The experiments were arranged using randomized completely block design (RCBD) with three replications for EC proliferation and randomized completely desaign (RBD) for EC regeneration. The results showed that combination of  aeration at 2.5 vvm and 10 g of EC was the most suitable aeration level and callus density for proliferation of EC in the 500 ml airlift bioreactor with 6.85 multiplication rate, 92.5% EC formation, and malformed callus morphology as low as 6.1%. The highest somatic embryos (SEs) formation was 87.7% with 44.5 SEs per clump and 92.1% SEs germination with 41.0 germinated-SEs per clump, 85.1% normal germinated-SEs, and whereas the best performance of plantlet was obtained from 1/2 MS + 0.05 mg L-1 BA semi solid medium. Plantlets were successfully acclimatized using Cycas rumphii medium with high survival rate (91.6%). Keywords: aerations, callus densities, germination, media, somatic embryos